3y3 - 12y2 + 4y = y(3y2 - 12y + 4) which cannot be factorised further.
12y2+1+15y2-10y-18y=27y2-28y+1. contact at saqibahmad81@yahoo.com
10x+4y+11xy
8x plus 4y equals 5 is 8x + 4y = 5.
It is the same as: 6x+4y
4y+6+9=4y+15
12y2+1+15y2-10y-18y=27y2-28y+1. contact at saqibahmad81@yahoo.com
10x+4y+11xy
8x plus 4y equals 5 is 8x + 4y = 5.
-7y + 4y = -3y
-y + -4y = -5y
-4x + 4y = 1
4y + 10 = 22 4y - 10 - 10 4y=12 4y 4y 4y=3
It is the same as: 6x+4y
1x plus 4y produces a 3 dimensional cuboid when it is graphed.
4y+6+9=4y+15
Oh, dude, you're hitting me with some math, huh? Well, technically, the answer for 3x + 4y is just 3x + 4y. I mean, you're not really simplifying it or anything, so that's all there is to it. Math can be a trip, man.
It simplifies to: 4y-16